Beyond the Green Revolution: A 10-Year Longitudinal Mixed-Methods Analysis of Balinese Subak Socio-Ecological Governance and its Alignment with SDG 2 and SDG 6 - Fitriyanti Fitriyanti; Anita Havyasari; Ni Made Nova Indriyani; Jasmila Tanjung; Matilda Munoz; Maya Enderson; Sudarto Sudarto (Indonesian Community Empowerment Journal, 2025)
The global challenges of food insecurity (SDG 2) and water scarcity (SDG 6) require proven, sustainable governance models. Socio-ecological systems (SES) rooted in local wisdom (kearifan lokal) offer resilient alternatives. The Balinese Subak, a UNESCO World Heritage site guided by the Tri Hita Karana philosophy, is a pre-eminent example. This research employed a 10-year (2015-2025) longitudinal, mixed-methods, comparative case study of two Subak systems in Bali. We collected a comprehensive dataset including 1,200 systematic water sampling events (yielding 7,200 analytical data points for pH, TSS, BOD, COD, NO3-N, PO4-P) and a 10-year rolling panel survey (n=2,000 completed survey-years) to assess agricultural and governance metrics. Qualitative data (n=60 interviews, n=24 meeting observations) were thematically analyzed. Generalized Linear Mixed-Effects Models (GLMMs) revealed a statistically significant time-dependent reduction in pollution, including Nitrate (β = -0.21 mg/L/year, p < .001) and BOD (β = -0.15 mg/L/year, p < .001), across both sites. This trend was strongly associated with a validated Social Governance Index (SGI). Critically, rice yields remained stable at a high-productivity average (6.2 t/ha), while chemical pesticide use declined by 48% (p < .001). Qualitative analysis identified the core mechanisms: (1) Tri Hita Karana as an internalized moral framework, (2) ritual calendars as coordination mechanisms, and (3) awig-awig as an adaptive governance system. In conclusion, the Subak system demonstrates a proven, sophisticated, and data-driven framework that operationalizes kearifan lokal to achieve the non-trade-off, simultaneous goals of sustainable agriculture (SDG 2) and clean water (SDG 6). These findings provide robust evidence that such systems are not relics but essential, adaptive governance models for global sustainability.